Is there any association between EBV infection and carotid artery stenosis? - Beyaz, Metin Onur; Agaçfidan, Ali; Önel, Mustafa; Öztaş, Didem Melis; Erdinç, İbrahim; Rodoplu, Orhan; Meriç, Mert; Ünal, Orçun; Conkbayır, Cenk; Uğurlucan, Murat (Czech Society of Cardiology Z.S, 2021)
Objective: Atherosclerosis is the mainly etiologic factor of coronary artery disease, carotid artery disease and peripheral artery disease. In our study, we aimed to show the presence and effect of Epstein-Barr virus (EBV) on the carotid artery stenosis leading chronic inflammatory process by producing pro-inflammatory cytokines and causing atherosclerosis. Material and methods: Between April 2017 and April 2018, thirty-six patients, who underwent carotid endarterectomy at Department of Cardiovascular Surgery, Istanbul University Istanbul Medical Faculty, are included in this study upon their consent. Each voluntary patient was initially recorded for age, sex, height and weight. Among 36 patients included in the study, 58.3% (n = 21) were male and 41.7% (n = 15) were female. The comorbidities such as hypertension, diabetes mellitus were considered. Results: There was not significant difference in EBV (DNA) positivity according to hyperlipidemia presence, sex, and age factors. However, the EBV (DNA) positivity was higher in the patients with co-morbidities such as hypertension and diabetes mellitus; no significant difference was detected. EBV (DNA) positivity in patients with bilateral carotid artery stenosis was 42.1% and it was 0% in patients without bilateral carotid artery stenosis (p: 0,002). The EBV (DNA) positivity was significantly higher in patients with bilateral carotid artery stenosis Conclusion: We believe that our significantly high EBV (DNA) rates in the patients with bilateral carotid artery stenosis may encourage the studies that claim the role of viral etiology on atherosclerosis, however, further studies are needed.
Keywords: Atherosclerosis; Carotid Artery Stenosis; EBV; Viral Etiology